Chemotherapy and mismatch repair deficiency cooperate to fuel TP53 mutagenesis and ALL relapse - Yang, Fan; Brady, Samuel W.; Tang, Chao; Sun, Huiying; Du, Lijuan; Barz, Malwine J.; Ma, Xiaotu; Chen, Yao; Fang, Houshun; Li, Xiaomeng; Kolekar, Pandurang; Pathak, Omkar; et al. (Nature cancer, 2021)
Chemotherapy is a standard treatment for pediatric acute lymphoblastic leukemia (ALL), which sometimes relapses with chemoresistant features. However, whether acquired drug-resistance mutations in relapsed ALL pre-exist or are induced by treatment remains unknown. Here we provide direct evidence of a specific mechanism by which chemotherapy induces drug-resistance-associated mutations leading to relapse. Using genomic and functional analysis of relapsed ALL we show that thiopurine treatment in mismatch repair (MMR)-deficient leukemias induces hotspot TP53 R248Q mutations through a specific mutational signature (thio-dMMR). Clonal evolution analysis reveals sequential MMR inactivation followed by TP53 mutation in some patients with ALL. Acquired TP53 R248Q mutations are associated with on-treatment relapse, poor treatment response and resistance to multiple chemotherapeutic agents, which could be reversed by pharmacological p53 reactivation. Our findings indicate that TP53 R248Q in relapsed ALL originates through synergistic mutagenesis from thiopurine treatment and MMR deficiency and suggest strategies to prevent or treat TP53-mutant relapse.